Pediatric lumbar disc herniation: A systematic review of the state of management strategies and outcomes (2010–2024) - Gerald Musa; Wila Namonje; Keith Simfukwe; Karina Marisel Familia; Bupe Mumba Mwela; Dimitri T. K. Ndandja; Manuel De Jesus Encarnacion Ramirez; Samuel Chilawa; Kachinga Agrippa Sichizya; Laston Chikoya; Gennady E. Chmutin; Andreas K. Demetriades (Journal of Craniovertebral Junction and Spine)
Introduction: Pediatric lumbar disc herniation (LDH) presents unique challenges compared to adult cases due to anatomical and developmental differences in the spine. This systematic review aims to consolidate evidence on the management and outcomes of pediatric LDH. Research Question: What are the clinical outcomes and efficacy of conservative and surgical treatments for pediatric LDH? Materials and Methods: A systematic review of studies from 2010 to 2024 was conducted following Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines. Databases including PubMed, Embase, Scopus, and Cochrane Library were searched for studies reporting on pediatric LDH treatment outcomes. Pain, disability, recurrence, and complication rates were extracted and assessed. The Joanna Briggs Institute checklist was used to evaluate bias. Results: The review included 861 pediatric patients across 14 studies, with a mean age of 14.88 years and a male predominance (59.6%). The most commonly affected levels were L5/S1 (53%) and L4/L5 (43.8%). Conservative treatment was employed in 9.9% (n = 66), whereas microdiscectomy, endoscopic discectomy, and fusion were performed in 53.7% (n = 360), 32.2% (n = 216), 4.2% (n = 28), respectively. Postoperatively, improvements in pain (Visual Analog Scale: 6.15–1.33) and disability (Oswestry Disability Index: 42.09–7.01) were noted. The recurrence rate was 1.7% postoperatively and 42.4% following conservative management (average follow-up period of 23.78 months). Complication rate was 3%. Discussion and Conclusion: Pediatric LDH is primarily associated with sports-related trauma. Minimally invasive techniques such as endoscopic and microdiscectomy demonstrate good early and long-term outcomes, and low complications and recurrence rates. There is a paucity of studies comparing management techniques, particularly ones discussing conservative management, which may represent underreporting.